Safety and efficacy of a feed additive consisting of Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) DSM 26571 for all animal species (Chr. Hansen A/S). (28th October 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Lactiplantibacillus plantarum (formerly Lactobacillus plantarum ) DSM 26571 when used as a technological additive intended to improve ensiling of forage. The additive is intended for use with all forages and for all animal species at a proposed application rate of 1 × 10 8 colony forming units (CFU)/kg fresh material. The bacterial species L. plantarum is considered by EFSA to be suitable for the qualified presumption of safety approach to safety assessment. As the identity of the strain has been clearly established and no acquired antimicrobial resistance determinants of concern were detected, the use of the strain as a silage additive is considered safe for livestock species, for consumers and for the environment. The additive is not irritant to skin or eyes and is not a skin sensitiser but should be considered a potential respiratory sensitiser. The FEEDAP Panel concluded that the addition of Lactiplantibacillus plantarum DSM 26571 at a minimum concentration of 1 × 10 8 CFU/kg may improve the production of silage from easy, moderately difficult and difficult to ensile forage material.